2018
DOI: 10.1007/s40264-017-0633-z
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Methods for Monitoring Adverse Events in Pediatric Psychopharmacology Clinical Trials

Abstract: Pediatric psychotropic prescription rates are rising, emphasizing the need for careful monitoring of drug safety in this population. Currently, no standardized assessments are used in clinical trials for adverse event (AE) elicitation focused on long-term drug treatment in pediatric patients. Despite a lack of standardized AE elicitation methods in psychiatric clinical trials, it is clear that psychiatric medications have developmentally dependent AEs that differ from those observed in adults. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…However, any comparison between the incidence and prevalence rates of ADRs reported in clinical trials is difficult to draw, as there are large differences in the classification systems, recorded periods, treatment settings, methods of data assessment, and patient and medication groups. Additionally, information about the severity of the ADRs is often missing 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, any comparison between the incidence and prevalence rates of ADRs reported in clinical trials is difficult to draw, as there are large differences in the classification systems, recorded periods, treatment settings, methods of data assessment, and patient and medication groups. Additionally, information about the severity of the ADRs is often missing 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Given these critical safety issues with potentially high impact on the individual patient and the resulting burden on health care systems, the importance of short- and long-term drug safety monitoring as well as the introduction of efficient pharmacovigilance methods in pediatric trials and as part of routine clinical practice have been increasingly recognized 21 22 27 30 31 . However, surveillance on ADRs is far from optimal, as appropriate monitoring practices are not yet established or were found to be inconsistent, and underreporting is still an unsolved problem 32 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, only few studies assessed AEs consistently or systematically. Unfortunately, this is a general problem in psychopharmacology ( Coates et al, 2018 ) and not unique for psychedelic drug studies. Instead, most studies relied on spontaneously reported and/or therapist-observed AEs.…”
Section: Discussionmentioning
confidence: 99%
“…As in any phase 2 study, priority was also given to identifying potential safety signals in this large population. To date, adverse event monitoring in pediatric trials of oxytocin have used a variety of methods, which is a prevalent issue across pediatric clinical trials in general [101]. The SOARS-B trial therefore moved to standardize AE monitoring by using a prospective systematic (body systems approach) elicitation of adverse events using the Systematic Longitudinal Adverse Events Scale (SLAES), complemented by both physical exam and monitoring of safety labs and ECG over the course of the trial.…”
Section: Discussionmentioning
confidence: 99%